Tourism Communication Strategy Pokdarwis Edelwais in Building Environmental and Culture-Based Ecotourism in the village of Ranu Pani. - Nabilah, Alfi Fatin; Safitri, Reza; Prasetyo, Bambang Dwi (Advances in Social Sciences Research Journal, 2023)
In terms of geomorphology and socio-culture, Ranu Pani Village has a lot of tourism potential that can be developed. However, this tourism progress does not go hand in hand with environmental sustainability in Ranu Pani Village. In minimizing the impact of natural damage caused by many factors, Pokdarwis Ranu Pani initiated a tourism concept that is based on local wisdom and is sustainable. This is known as the concept of ecotourism. Pokdarwis cooperates with various elements to realize ecotourism in Ranu Pani Village. This research uses a descriptive method with a qualitative approach. Researchers made direct observations in the field to collect data by conducting interviews, observation and documentation. The results showed that the tourism communication strategy carried out by Pokdarwis Ranu Pani was effective because it was supported by good synergy between Pokdarwis when it involved the government, community, outsiders, academics and institutions related to ecotourism in developing ecotourism in Ranu Pani Village.